Maternal and fetal outcomes of uterine rupture and factors associated with maternal death secondary to uterine rupture - Astatikie, Geremew (BMC Pregnancy Childbirth, 2017)
BACKGROUND: Maternal mortality and morbidity are the priority agenda for sub-Saharan Africa including Ethiopia. Uterine rupture is the leading cause of maternal and fetal death in developing countries. Limited evidence is available on the magnitude of uterine rupture; maternal and fetal outcomes of uterine rupture and factors associated with maternal death secondary to uterine rupture in Ethiopia. This study aimed to assess the magnitude of uterine rupture; maternal and fetal outcome of uterine rupture and factors associated with maternal death secondary to uterine rupture in Debremarkos Referral Hospital, Northwest Ethiopia. METHODS: An institutional-based cross-sectional study was conducted in December 2015 in Debremarkos referral hospital, Northwest Ethiopia. A total of 242 records of mothers with uterine rupture at Debremarkos referral Hospital during the year 2011–2014 were included in the study. Secondary data was collected from the records of mothers admitted for the management of uterine rupture. Descriptive statistics were performed to characterize the study population. Bivariate and multivariable logistic regression model was fitted to identify factors associated with maternal death secondary to uterine rupture. Odds ratio with 95% confidence interval was computed to determine the level of significance. RESULTS: A total of 10,379 deliveries were attended A total of 242 uterine rupture cases were included in this study. The magnitude of uterine rupture was 2.44% (1 in 41 deliveries). Sixteen (6.6%) mothers died from uterine rupture. Fourteen (5.8%) had experienced Vesico Vaginal Fistula. The majority of the mothers, 72% (176), admitted for uterine rupture stayed in hospital for 6–10 days. Fetal outcome was grave, 98.3% (238) were stillborn. Place of labor [Adjusted odds ratio (AOR): 6.92, 95% confidence interval (CI): (1.16, 33.74)], occurrence of hypo volume shock [AOR: 3.48, 95% CI: (1.01, 11.96)] and postoperative severe anemia [AOR: 0.092, 95% CI: (0.01, 0.956)] were significantly associated with maternal death secondary to uterine rupture. CONCLUSION: The magnitude of uterine rupture was high in the study area. Initiation of labor at health institutions, early treatment of hypo-volumia and prevention of postoperative anemia is recommended to decrease maternal death secondary to uterine rupture.